Atmospheric-variational pressure-saturated water characteristics of medium-high rank coal reservoir based on NMR technology. (15th November 2019) - Yang, Zhaobiao; Peng, Hui; Zhang, Zhengguang; Ju, Wei; Li, Geng; Li, Cunlei
Highlights: The water saturation of medium rank coal is lower than that of high rank coal. A calibration method of saturable pore diameter ( d *) is established. The coal rank has a power relationship with the d *. When the d * is between 1 and 10 nm, the Sw typically exceeds 60%. Abstract: The fluidity of medium-high rank coal reservoirs is different at the microscopic scale, which can lead to differences in coalbed methane (CBM) production. Taking the medium-high rank coal reservoirs in eastern Yunnan and western Guizhou as examples, the characteristics of atmospheric-variational pressure-saturated water based on nuclear magnetic resonance (NMR) technology were studied. The results show that under atmospheric pressure and vacuum pressure, the water saturation ( Sw ) of medium rank coal is lower than that of high rank coal; the former is less than 50%, and the latter is more than 60%, which is attributed to the higher developed micropores and hydrophilicity of high rank coal. With an increase in the saturation pressure, the Sw of medium-high rank coal is not evident. A conversion method of the T 2 spectrum and the low-temperature liquid nitrogen average pore size are proposed. Thus, the calibration method of the minimum pore size that water can enter under atmospheric-variational pressure conditions is established, and the saturable pore diameter ( d *) under atmospheric-variational pressure conditions is obtained. Under natural atmospheric pressure, water can enter the micropores and transition pores (pore diameter d < 100 nm). The higher the coal rank is, the smaller the d * is. Most of the high rank coal can enter the micropores (pore diameter d < 10 nm). As the saturation pressure increases, the d * of the medium-high rank coal gradually decreases. Under different saturation conditions, the coal rank has a power relationship with the d *. As the d * decreases, the Sw increases.